The mediating effect of leader–member exchange in relationship with emotional intelligence, job satisfaction, and turnover intention - Ali Gholipour Soleimani; Hannaneh Einolahzadeh (Cogent Business & Management, 2017)
The purpose of this research is to study the mediating effect of leader–member exchange quality variable in the relationship between emotional intelligence and turnover intention and job satisfaction of employees. In terms of methodology, this is a survey correlational research. Statistical population included the staff of Sayeh Sabz Oloum Company in Tehran-Iran that all members of the population were studied. Research data were collected through questionnaires. Reliability was accepted by Cronbach’s alfa coefficient and validity was accepted by confirmatory factor analysis. Data analysis and research hypothesis testing was performed through structural equation modeling and hierarchical multiple regression. Two softwares (SPSS and LISREL), also were used for statistical processing. The results showed the mediating effect of leader–member exchange in quality variable did not have any effect on relationship between emotional intelligence and job satisfaction and turnover intention. Emotional intelligence skills had positive relationship with job satisfaction, but had negative relationship with turnover intention. In other words, emotional intelligence improves staff’s attitude toward decreasing turnover and increasing job satisfaction. Job satisfaction also causes reduction in turnover.